Prenatal Activation of Toll-Like Receptor-4 Dampens Adult Hippocampal Neurogenesis in An IL-6 Dependent Manner - Mouihate, Abdeslam (Frontiers in Cellular Neuroscience, 2016)
Prenatal immune challenge has been associated with alteration in brain development and plasticity that last into adulthood. We have previously shown that prenatal activation of toll-like receptor 4 by LPS induces IL-6-dependent STAT-3 signaling pathway in the fetal brain. Whether this IL-6-dependent activation of fetal brain results in long lasting impact in brain plasticity is still unknown. Furthermore, it has been shown that prenatal LPS heightens the hypothalamic-pituitary-adrenal (HPA) response in adulthood. In the present study we tested whether LPS administration during pregnancy affects neurogenesis in adult male offspring. Because corticosterone, the end-product of HPA axis activity in rats, alters neurogenesis we tested whether this enhanced HPA axis responsiveness in adult male offspring played a role in the long lasting impact of LPS on neurogenesis during adulthood. Pregnant rats were given either LPS, or LPS and an IL-6 neutralizing antibody (IL-6Ab). The newly born neurons were monitored in the subventricular zone (SVZ) and the dentate gyrus (DG) of the hippocampus of adult male offspring by monitoring doublecortin and T-box brain protein 2 expression: two well-established markers of newly born neurons. Prenatal LPS decreased the number of newly born neurons in the DG, but not in the SVZ of adult offspring. This decreased number of newly born neurons in the DG was absent when IL-6Ab was co-injected with LPS during pregnancy. Furthermore, administration of a corticosterone receptor blocker, RU-486, to adult offspring blunted the prenatal LPS induced decrease in newly born neurons in the DG. These data suggest that maternally triggered IL-6 plays a crucial role in the long lasting impact of LPS on adult neurogenesis.